FURTHER DEVELOPMENT OF THE GERENTOLOGICAL ESSENCE OF EDUCATING THE FUTURE GENERATION IN NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2026)
This article analyzes state policy and practical measures aimed at social protection of representatives of the older generation in Uzbekistan, providing them with material and moral support. The article emphasizes the role of the elderly in society and the upbringing of youth, and the elevation of respect for them to the level of a national idea. In particular, the activities of the "Nuroniy" Foundation, state-allocated benefits, provision of medicines and medical services, and care for war and labor veterans are widely covered. It is also noted that supporting the elderly remained a priority of state policy even during the pandemic. The information presented in the article demonstrates the effectiveness of reforms to protect the older generation.